2016
DOI: 10.3341/kjo.2016.30.6.426
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Vitamin D and Glaucoma: A Kangbuk Samsung Health Study

Abstract: PurposeTo investigate the relationship between vitamin D and glaucoma.MethodsThis retrospective, cross-sectional study included subjects who underwent a health screening at the Health Screening Center of Kangbuk Samsung Hospital from August 2012 to July 2013. All fundus photographs were reviewed by ophthalmologists. The ophthalmologists determined if an eye was glaucomatous based on the criteria set forth by the International Society of Geographical and Epidemiological Ophthalmology and by the appearance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
2
34
1
Order By: Relevance
“…This dividing analysis method was used to it at previous study with blood chemistry data [13]. History of thyroid abnormalities and newly diagnosed subjects were classified into hypothyroidism, hyperthyroidism, thyroid nodular cyst, and thyroid hormone treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dividing analysis method was used to it at previous study with blood chemistry data [13]. History of thyroid abnormalities and newly diagnosed subjects were classified into hypothyroidism, hyperthyroidism, thyroid nodular cyst, and thyroid hormone treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were divided equally into four groups (quartiles) based on thyroid laboratory testing as follows: thyroid-stimulating hormone (TSH, μ IU/mL) quartiles, Q1 (TSH < 1.30), Q2 (1.30 ≤ TSH < 1.90), Q3 (1.90 ≤ TSH < 2.75), and Q4 (TSH ≥ 2.75); free thyroxine (free T4, ng/dL) quartiles, Q1 (free T4 < 1.15), Q2 (1.15 ≤ free T4 < 1.26), Q3 (1.26 ≤ free T4 < 1.38), and Q4 (free T4 ≥ 1.38); and triiodothyronine (T3, pg/mL) quartiles, Q1 (T3 < 2.87), Q2 (2.87 ≤ T3 < 3.12), Q3 (3.12 ≤ T3 < 3.40), and Q4 (T3 ≥ 3.40). This dividing analysis method was used to it at previous study with blood chemistry data [ 13 ]. History of thyroid abnormalities and newly diagnosed subjects were classified into hypothyroidism, hyperthyroidism, thyroid nodular cyst, and thyroid hormone treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D plays a role in the signaling pathways related to bone and mineral metabolism, cellular proliferation, immune modulation, and oxidative stress [169,170]. A high prevalence of vitamin D deficiency is observed in patients with glaucoma, confirmed by low circulating amounts of vitamin D in these subjects [171,172]. Metabolomic analysis on plasma samples from 72 POAG patients compared to 72 healthy controls revealed alterations of vitamin D metabolic pathways correlating with vitamin D insufficiency in POAG patients [173]; moreover, the presence of specific vitamin D receptor polymorphisms were found to be relevant risk factors in the development of glaucoma [174].…”
Section: Food Supplementsmentioning
confidence: 99%
“…Based on a recent review by Reins and McDermott (130), studies of vitamin D in the eye have been focused on myopia, retinoblastoma, age-related macular degeneration, diabetic retinopathy, uveitis, and glaucoma. Epidemiological studies revealed a reverse association between serum vitamin D levels and the prevalence of myopia (35,53), AMD (14,115), diabetic retinopathy (4,116,117), dry eye syndrome (182), tear hyperosmolarity and tear film dysfunction (45), and open angle glaucoma (in the Korean population) (181) with elevated risk of glaucoma in females (84). Serum levels of 25(OH)D 3 were significantly lower in neovascular AMD compared with non-neovascular AMD and control groups (71), further supporting a direct role for vitamin D in the regulation of angiogenesis.…”
Section: Vitamin D and Eye Diseasesmentioning
confidence: 99%